Reações de ciclização eletrofílica intramolecular de 2-butilselenofenilprop-1-in-3- ois promovida por I2 para a síntese de benzo[b]selenofenos - Pistoia, Renan Piovesan (2015)
In the present work, we reported the synthesis of a series of heterocycles via electrophilic intramolecular cyclization of (2-(butylselanyl)phenyl)-3-phenylprop-2-yn-1 1, for the synthesis of benzo[b]selenophene 2, mediated by I2. In the first, report the synthesis of (2-(butylselanyl)phenyl)-3-phenylprop-2-yn-1 1 promoted by the addition reaction lithium alkynyl anion to the aldehydes was performed, subsequently cyclized using I2 in ethanol as solvent at room temperature. In the present study were obtained their products in moderate to good yields. In order to evaluate the versatility of benzo[b]selenophene 2 was submitted of cyanation reaction for obtaining benzo[b]selenophene -2- carbonitrile 3 in 82% yield. furthermore, the addition of alkyne anions to carbonyl of benzoselenofenos 2 gave 1- (benzo[b]selenophen-2-il)-1-phenyl-3-p-tolylprop-2-in-1-ol 4 in 62% yield. Subsequently, the intramolecular cyclization reaction of compound 4 with BuSeBr gave the [ 3,2- b] benzoselenofeno -2-yl (p- tolyl ) methanone 5 in 53% yield.